Morphogenesis of Pancreas in Buffalo during prenatal life - Gupta, Divya; Uppal, Varinder; Bensal, Neelam; Gupta, Anuradha (Indian Journal of Veterinary Anatomy, 2018)
The study was conducted on pancreas of 24 buffalo foetii collected from slaughter house and Veterinary clinics, GADVASU, Ludhiana. The approximate age of the foetii was estimated by measuring the CVRL. The foetii were divided into three groups; Group I = CVR length up to 20 cm, Group II = CVR length 20 cm to 40 cm and Group III = CVR length above 40 cm. The pancreas was dissected out from the abdominal cavity and the tissues werefixed in 10% Neutral buffered formalin and processed for paraffin sectioning. The paraffin sections were stained with Hematoxylin & Eosin, Masson’s trichrome for collagen fibres, Gridley’s silver stain for reticular fibres and Verhoeff stain for elastic fibres. In group I, at 9.6 cm CVRL (72 days), the pancreas was observed as lobulated organ situated transversely on the dorsal wall of abdomen and comprised of two lobes i.e. splenic or left lobe and duodenal or right lobe. The mesenchymal tissue was having mesenchymal cells, very few fibroblasts, fine collagen fibrils enclosing the primitive pancreatic tubules. At 12.8 cm CVRL (86 days), the connective tissue trabaculae fromcapsule invaded and divided the organ into lobes and lobules. In group II, at 28.3 cm CVRL (137 days), both the lobes showed extensive growth but still the splenic lobe was larger as compared to duodenal lobe. At 28.3 cm CVRL (137 days), the capsule was better differentiated comprising of large number of collagen fibres, fibroblasts, few mesenchymal cells and few reticular fibres. Large number of blood capillaries and ganglia along with myelinated and non myelinated nerve fibres were observed. In group III, at 48 cm CVRL (182 days), the duodenal lobe almost completely filled the mesentery between two loops of duodenum and splenic lobe was further extended across the stomach to the intestine. Near end of the gestation period, at 100.5 cm CVRL (300 days), the entire connective tissue was occupied by parenchyma of pancreas.